2006
DOI: 10.1128/cvi.00229-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Enzyme Immunoassay for Detection of Dengue Virus NS1 Antigen in Human Serum

Abstract: We evaluated a one-step sandwich-format microplate enzyme immunoassay for detecting dengue virus NS1 antigen (Ag) in human serum by use of Platelia Dengue NS1 Ag kits (Bio-Rad Laboratories, Marnes La Coquette, France). We collected 299 serum samples from patients with dengue disease and 50 serum samples from patients not infected with dengue virus. For the 239 serum samples from patients with acute infections testing positive by reverse transcription-PCR and/or virus isolation for one of the four dengue virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
157
2
9

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(183 citation statements)
references
References 23 publications
(14 reference statements)
13
157
2
9
Order By: Relevance
“…Dussart et al (2006) reported a similar finding for the performance of the Platelia Dengue NS1 Antigen ELISA assay. Though our analysis showed reduced sensitivity of Dengue Early assay for the detection of DENV3 serotype, more samples are needed to confirm this observation.…”
Section: Ns1 Antigen Assays For Dengue Diagnostics and Surveillancesupporting
confidence: 69%
See 1 more Smart Citation
“…Dussart et al (2006) reported a similar finding for the performance of the Platelia Dengue NS1 Antigen ELISA assay. Though our analysis showed reduced sensitivity of Dengue Early assay for the detection of DENV3 serotype, more samples are needed to confirm this observation.…”
Section: Ns1 Antigen Assays For Dengue Diagnostics and Surveillancesupporting
confidence: 69%
“…Evaluation of these assays (Dussart et al 2006, Kumarasamy et al 2007, Blacksell et al 2008, Lapphra et al 2008) has demonstrated high sensitivity and specificity for DENV detection, particularly during the acute phase of the disease. In this study, we evaluated the performance of three commercially available dengue NS1 antigen assays, in comparison with other widely used dengue diagnostic assays, to determine the usefulness of NS1 antigen assays in early diagnosis of dengue in a primary healthcare setting in Singapore.…”
Section: Vector-borne and Zoonotic Diseasesmentioning
confidence: 99%
“…This assay provides additional dengue diagnostic tool to the existing approaches of PCR, antibody capture ELISA and virus isolation 5,6,10,12,13,20,24,25,28 . Even though NS1 is a sensitive methodology for the detection of DENV it should never be used as the only methodology for DENV detection because it doesn't identify different serotypes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…NS1 is a structural protein that is produced in both membrane-associated and secreted forms. It is involved in viral replication and has been shown to correlate with viremia (Libraty et al 2002, Dussart et al 2006 Environmental Health Institute, National Environmental Agency, Singapore, Singapore. DOI: 10.1089DOI: 10.…”
mentioning
confidence: 99%